Humanized Microhistory of Translation: The Case of Modern Arabic Literature in English Translation - Al-Batineh, Mohammed (Jordan Journal of Modern Languages & Literatures, 2022)
Throughout history, translators have played a vital role as cultural agents in shaping the histories of different nations and cultures. Nevertheless, the translators’ role has been largely ignored in translation history research studies, which have often focused on the texts translated. Therefore, many scholars in translation history research (Adamo 2006; Munday 2014; Pym 2009) have argued for the importance of studying translators themselves. The present study draws on the method of microhistory and applies it to the Arabic translation tradition by analyzing the life, personal relationships, and statements of one of the leading translators of Modern Arabic Literature (MAL) into English, Denys Johnson-Davies (J-D). The paper explores and analyses J-D’s autobiography, interviews, and paratextual materials accompanying his translations in order to better understand how J-D’s experience as a translator and cultural agent can shed light on the bigger picture of MAL translation history. The data analysis reveals insights into the status of translation during the different periods of MAL translation history. This includes the publication of Arabic-translated literary works into English, the reception of MAL by the English readership, and the reception of translators and their work by Arab authors and governments during the different periods of the translation history of MAL. This study also confirms the argument that the study of translators is a valid, useful method for researching translation history. Keywords: Modern Arabic Literature, Translation Microhistory, Arabic Translation history, Denys Johnson-Davies, Humanizing translation history, Translator Studies